Time variant system identification of superstructures of base-isolated buildings. (1st November 2021) - Hernández, Francisco; Díaz, Pablo; Astroza, Rodrigo; Ochoa-Cornejo, Felipe; Zhang, Xihong
Highlight: Time-variant properties related to superstructures are identified from seismic data. A novel Short Time Transfer Function (STTF) has been implemented. STDSI and STTF results are comparable and allow estimating substructure properties. The methodology is valid for analytical, experimental and actual BI buildings. The superstructures' dynamic properties are comparable with a FB building. Abstract: The time-variant dynamic properties related to the superstructure of base-isolated (BI) buildings are identified using a simple substructure approach. Based on the acceleration data recorded in BI buildings during earthquake events, the short-time deterministic-stochastic subspace identification (STDSI) method and a novel short-time transfer function (STTF) method are used to identify the temporal evolution of the modal properties of the superstructure, which can be consequently employed to study the evolution of its potential damage. The proposed substructure approach is applied to experimental data from three BI structures: a building numerically simulated using the commercial software SAP2000, a full-scale five-story reinforced concrete BI building tested at different intensity levels on a large-scale shake table, and an instrumented four-story reinforced masonry building located in Chile. The results indicate that the identified modal properties obtained for the superstructure by using the proposed approach are comparable to those obtained from the corresponding fixed-base (FB) buildings, allowing to study in detail the dynamic behavior of BI buildings' superstructures disaggregating the highly inelastic response associated with the seismic isolation system.